Regulatory and Sustainability Perspectives in Pension Fund Management: A Comparative Analysis - Eliza Eliza; Ahadi Rerung; Subur Harahap; Joni Devitra; Dwi Irawati (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Pension fund management in Southeast Asia faces challenges due to aging populations, economic volatility, and varying regulatory frameworks. This study investigates pension fund management practices in Singapore, Indonesia, Malaysia, Thailand, and the Philippines to identify factors influencing their sustainability. The objective is to compare regulatory frameworks, investment strategies, and demographic challenges to provide insights for policy reforms. Using a qualitative comparative analysis, the study examines data from government reports, academic articles, and industry publications. The findings reveal that Singapore’s strong regulatory system and diversified investments ensure high sustainability, while Indonesia struggles with limited regulations, low coverage (only 16.5% of workers), and conservative investment approaches. Malaysia, Thailand, and the Philippines face similar issues, with moderate sustainability due to weak oversight and reliance on low-yield assets. Demographic pressures, such as increasing dependency ratios, further strain these systems. The study concludes that tailored reforms, including expanding coverage to informal sectors and diversifying investments into assets like infrastructure, are essential to enhance pension system sustainability across Southeast Asia. These insights contribute to understanding regional pension management and offer practical recommendations for policymakers to secure long-term financial stability for retirees.